Women in Nuclear Power Programs: Case Studies from Africa - Jessica S Burniske; Chanel Chauvet-Maldonado; Beth Kaboro; Madalina Man; Susan Nalumansi (International Journal of Nuclear Security, 2023)
Approximately 30 countries are considering, planning, or starting nuclear power programs, and nearly 20 more countries have expressed interest in nuclear power. Most of these countries are nuclear newcomers. According to the International Atomic Energy Agency (IAEA), a nuclear power program is a major undertaking requiring careful planning, preparation, and investments in institutions and human resources because of the safety, security, and safeguards requirements associated with the use of nuclear energy. The IAEA Milestones Approach states that states should follow three phases of development to establish the necessary infrastructure for a nuclear power program. Nuclear security is one of the 19 infrastructure issues considered throughout the three phases, alongside other infrastructure issues such as human resource development and legal and regulatory development. Despite the number of countries operating or interested in developing nuclear power plants, women comprise less than a quarter of the nuclear sector workforce. New nuclear power programs require a skilled and diverse workforce to build the necessary infrastructure and sufficiently address nuclear security. The underrepresentation of women in the field affects competitiveness, effectiveness, and diversity, and new nuclear power programs represent an opportunity to advance gender equality in nuclear security. This paper analyzes existing international, regional, and national gender equality measures and describes how a country’s nuclear power program can integrate those measures. It examines experiences from two Eastern Africa nuclear newcomers: Kenya and Uganda. Finally, the paper presents recommendations and potential solutions to address gender equality in nuclear security.
Keywords: Nuclear security; gender; gender equality; nuclear newcomers; IAEA